Bone mechanical properties and changes with osteoporosis. (June 2016) - Osterhoff, Georg; Morgan, Elise F.; Shefelbine, Sandra J.; Karim, Lamya; McNamara, Laoise M.; Augat, Peter
Abstract: This review will define the role of collagen and within-bone heterogeneity and elaborate the importance of trabecular and cortical architecture with regard to their effect on the mechanical strength of bone. For each of these factors, the changes seen with osteoporosis and ageing will be described and how they can compromise strength and eventually lead to bone fragility.